Kinetics of Periodate Oxidation of Aromatic amines-A Comparison of Effect of pH on Oxidation of Some Anilines - Kaushik, R.D.; Joshi, Rajesh (Asian Journal of Chemistry, 2010)
The effect of pH on kinetics of oxidation of seven aromatic amines has been studied in acetone-water medium. The results have been compared and some of these have been found to differ from the trend reported in the earlier works.